Phase Transformations During Heat Treatment of a CPM AISI M4 Steel - Maribel L. Saucedo-Muñoz; Valeria Miranda-Lopez; Felipe Hernandez-Santiago; Carlos Ferreira-Palma; Victor M. Lopez-Hirata (Metals)
The phase transformations of Crucible Particle Metallurgy (CPM) American Iron and Steel Institute (AISI) M4 steel were studied during heat treatments using a CALPHAD-based method. The calculated results were compared with experimental observations. The optimum austenitizing temperature was determined to be about 1120 °C using Thermo-Calc software (2024b). Air-cooling and quenching treatments led to the formation of martensite with a hardness of 63–65 Rockwell C (HRC). The annealing treatment promoted the formation of the equilibrium ferrite and carbide phases and resulted in a hardness of 24 HRC. These findings with regard to phases and microconstituents are in agreement with the predictions derived from a Thermo-Calc-calculated time–temperature–transformation diagram at 1120 °C. Additionally, the primary carbides, MC and M6C, which formed prior to the heat treatment and had a minor influence on the quenched hardness. In contrast, the tempering process primarily led to the formation of fine secondary M6C carbides, which hardened the tempered martensite to 57 HRC. The present work demonstrates the application of a CALPHAD-based methodology to the design and microstructural analysis of tool steels.